2014
DOI: 10.5489/cuaj.1362
|View full text |Cite
|
Sign up to set email alerts
|

Double anticholinergic therapy for refractory neurogenic and non-neurogenic detrusor overactivity in children: Long-term results of a prospective open-label study

Abstract: Introduction: In this study, we optimize pharmacotherapy in children who failed anticholinergic monotherapy by simultaneous administration of 2 anticholinergics (oxybutynin and/or tolterodine and/or solifenacin). Methods: This report is an update of our previously published study on double anticholinergic regimen in children with refractory incontinence due to neurogenic (NDO) and non-neurogenic (DO) detrusor overactivity. Patients with an insufficient response (clinically/urodynamically) to an optimized dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…47 In a 36-month extension phase of this study including 56 patients, 41% of patients were dry and 32% were improved; 50% experienced mild or moderate side effects, with two patients requiring a different treatment regimen because of troublesome side effects. 48 Our group also recently reported on a prospective, open-label study to assess dual therapy with an antimuscarinic agent and mirabegron. Our results are promising, with improvement of continence in all 35 patients and mild side effects in only four patients.…”
Section: Dual Therapymentioning
confidence: 99%
“…47 In a 36-month extension phase of this study including 56 patients, 41% of patients were dry and 32% were improved; 50% experienced mild or moderate side effects, with two patients requiring a different treatment regimen because of troublesome side effects. 48 Our group also recently reported on a prospective, open-label study to assess dual therapy with an antimuscarinic agent and mirabegron. Our results are promising, with improvement of continence in all 35 patients and mild side effects in only four patients.…”
Section: Dual Therapymentioning
confidence: 99%
“…Combined antimuscarinic agents were used in some of our patients. It has been reported that combined antimuscarinic agents could provide good clinical and urodynamic effects for elderly, refractory, neurogenic or even child OAB patients . However, while a β3‐adrenoceptor agonist is available, a combination of antimuscarinics and mirabegron may be a good alternative for refractory OAB patients to avoid additive adverse effects of combined antimuscarinic agents …”
Section: Discussionmentioning
confidence: 99%
“…Dr. Bolduc has pioneered increasing dosing and combining antimuscarinics to increase efficacy and minimize side effects. 23 Once adult dosing has been reached with a single medication, a second antimuscarinic is well-tolerated and may result in continence or safer bladder pressures. 23 In our patients who have persistent hydronephrosis despite maximal medical management, overnight catheter drainage can be attempted.…”
Section: Elementary Schoolmentioning
confidence: 99%
“…23 Once adult dosing has been reached with a single medication, a second antimuscarinic is well-tolerated and may result in continence or safer bladder pressures. 23 In our patients who have persistent hydronephrosis despite maximal medical management, overnight catheter drainage can be attempted. Since the highest bladder volumes, and therefore pressures, will likely occur overnight, continuous overnight drainage may decrease renal stress.…”
Section: Elementary Schoolmentioning
confidence: 99%
See 1 more Smart Citation